Peningkatan Layanan Smart Pemilu Berbasis Website dengan Memanfaatkan Teknologi Canggih Internet of Things (IoT) di KPU Kabupaten Probolinggo - Fadhil Rahman; Moh. Anggi Cahyono; Moh. Fedi Hermawan; Moh. Nawawi; Moh. Farhan Faradika (Insan Kreasi Media, 2022)
The development of the times and election issues from the village level to the provincial level, a Field Election Supervisory Committee (PPl) was formed at the village level. Ratio based on polling stations (TPS), which is between 1 to 20 TPS supervised by 1 (one) Field Election Supervisor (PPL) and from 21 to 30 supervised 2 PPL and 31 to 50 TPS supervised 3 PPL, between 50 more supervised 5 PPL and so on, With the smart election tool using an IOT (Internet of Thing) based website. Where the tool is a configuration system for two studies, namely RFID-based IOT (Internet Of Thing) with a Web-based database input system. so that the voting rights data storage will be directly stored in the database and can be used periodically in ongoing elections. The stored data will be automatically accumulated every election season, so that election officials do not need more time and energy to recapitulate the election and this system will be tested in general election simulations with related parties at the Pobolinggo City KPU office.